Identification of mercury‐resistant Streptomyces isolated from Cyperus rotundus L. rhizosphere and molecular cloning of mercury (II) reductase gene - Wahyu Aristyaning Putri; Hanum Mukti Rahayu; Anis Uswatun Khasanah; Langkah Sembiring; Masashi Kawaichi; Yekti Asih Purwestri (Universitas Gadjah Mada, 2021)
Streptomyces is one of mercury‐resistant bacteria which can convert Hg2+ into nontoxic Hg0 . This study aimed to identify mercury‐resistant Streptomyces present in the Cyperus rotundus rhizosphere from artisanal small‐scale gold mining (ASGM) area and clone merA gene to the cloning and expression vectors. Molecular identification was conducted using 16s rRNA gene with the maximum likelihood algorithms. Results revealed that the AS1 and AS2 strains were a group of Streptomyces ardesiacus and the BR28 strain was closed to Brevibacillus agri. The AS2 merA gene was cloned to pMD20 cloning vectors, pGEX‐5x‐1 and pET‐28c expression vectors. The transformation was successfully performed in BL21 and DH5α competent cells. The full length of the merA gene was confirmed to be 1,425 bp. This study is the first research on identifying mercury‐resistant Streptomyces and cloning the full‐length merA gene in Indonesia.